Beyond the lesion: neuroimaging foundations for post-stroke recovery. (September 2013) - Carey, Leeanne M; Seitz, Rüdiger J; Parsons, Mark; Levi, Christopher; Farquharson, Shawna; Tournier, Jacques-Donald; Palmer, Susan; Connelly, Alan
A shift is emerging in the way in which we view post-stroke recovery. This shift, supported by evidence from neuroimaging studies, encourages us to look beyond the lesion and to identify viable brain networks with capacity for plasticity. In this article, the authors review current advances in neuroimaging techniques and the new insights that they have contributed. The ability to quantify salvageable tissue, evidence of changes in remote networks, changes of functional and structural connectivity, and alterations in cortical thickness are reviewed in the context of their impact on post-stroke recovery. The value of monitoring spared structural connections and functional connectivity of brain networks within and across hemispheres is highlighted.